2018
DOI: 10.7759/cureus.3254
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in Advanced Non-small Cell Lung Cancer Patients: Ushering Chemotherapy Through the Checkpoint Inhibitors?

Abstract: New ways of exploiting the immune system for cancer treatment have been tested for decades with moderate outcomes. Based on previous immunotherapy knowledge, agents targeting immune checkpoints seem to be remarkably effective in a wide range of tumors. Immune checkpoint inhibitors in metastatic non-small cell lung cancer (NSCLC) provide longlasting responses in specific patients. Nevertheless, with overall response rates ≤ 20%, combinational protocols for various patient subgroups are needed. A good partner tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…However, in our study, we reported no correlation between CSCs and CD4+ cells. We believe that these data reflect what has been previously described in the literature for solid tumors (27)(28)(29)(30)(31)(32)(33)(34)(35), defining additional roles for CD4+ T cells, some of which are independent of other lymphocytes, that influence and/or contribute to tumor immunity during carcinogenesis. Consequently, our findings may underline the dualistic role of CD4+ T cells in antitumor activity (33).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, in our study, we reported no correlation between CSCs and CD4+ cells. We believe that these data reflect what has been previously described in the literature for solid tumors (27)(28)(29)(30)(31)(32)(33)(34)(35), defining additional roles for CD4+ T cells, some of which are independent of other lymphocytes, that influence and/or contribute to tumor immunity during carcinogenesis. Consequently, our findings may underline the dualistic role of CD4+ T cells in antitumor activity (33).…”
Section: Discussionsupporting
confidence: 87%
“…The CD8+/Treg ratio was also a potential predictor of response to immunotherapy in mouse models of pancreatic cancer (27), which further supports its potential as an important biomarker and even a driver of the response to immunotherapy. Recent clinical studies are encouraging, showing that immunotherapy for lung cancer alone or in combination with conventional treatments significantly improves patient outcomes (27). However, the exact immune cell composition in NSCLC is not clear, and the scientific community is focusing their attention on specific intratumoral cell compositions that are represented by TILs (24).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Immune modulating therapies have demonstrated tremendous efficacy for malignancies such as melanoma and non-small cell lung cancer 1 , 2 . On the other hand, colorectal cancer (CRC) seems to respond differently based on whether or not the tumor has deficient DNA mismatch repair mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…However, this result seems to be contradictory to the previous reports. High concentration of TILs was reported to correlate with improved disease free survival and decreased risk of recurrence in lung cancer (6)(7)(8)(9), whereas cancer stem cell (CSC) is generally linked to tumor recurrence and metastasis (10,11). CD133 has been widely used as a CSC marker in NSCLC (12).…”
mentioning
confidence: 99%